2017
DOI: 10.4209/aaqr.2017.09.0308
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Particle Partitioning of Polychlorinated Dibenzo-p-dioxins, Dibenzofurans, and Biphenyls in Flue Gases from Municipal Solid Waste Incinerators

Abstract: Gas-particle partitioning of polychlorinated dibenzo-p-dioxins, dibenzofurans (PCDD/Fs), and biphenyls (PCBs) was evaluated in flue gases emitted from two municipal solid waste incinerators. Total PCDD/Fs and dl-PCBs in the flue gas were presented, in decreasing order, within gas phases, particulate phases, and aqueous phases. PCDD/F concentrations in the flue gas ranged from 0.75 to 15 ng m -3 , while in the particulate phase they ranged from 0.14 to 8.1 ng m -3 . Dioxin-like (dl-) PCBs had concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 46 publications
(51 reference statements)
1
2
0
Order By: Relevance
“…From the viewpoint of the contribution to the total I-TEQ values (as shown in Fig. 6(b)), the greatest contributor was 2,3,4,7,8-PeCDF (36.72-38.66%), which was a similar finding to that of other researchers (Han et al, 2017;Hsieh et al, 2018;Lin et al, 2018;Zhan et al, 2018).…”
Section: Profiles Of the Homologs And Congeners Of Pcdd/fs In The Fly Ash Collected From The Baghousesupporting
confidence: 87%
“…From the viewpoint of the contribution to the total I-TEQ values (as shown in Fig. 6(b)), the greatest contributor was 2,3,4,7,8-PeCDF (36.72-38.66%), which was a similar finding to that of other researchers (Han et al, 2017;Hsieh et al, 2018;Lin et al, 2018;Zhan et al, 2018).…”
Section: Profiles Of the Homologs And Congeners Of Pcdd/fs In The Fly Ash Collected From The Baghousesupporting
confidence: 87%
“…Typical organic pollutants, such as polychlorinated dibenzo-p-dioxins and polychlorinated dibenzofurans (PCDD/Fs), chlorobenzenes (CBzs) and chlorophenols, can be found throughout the whole process of municipal solid waste incinerator (MSWI) with various concentration levels. Researchers have found that there are various persistent organic pollutants in the bottom ash, fly ash and the flue gases before and after the air pollution control devices (APCDs) (Dong et al, 2002;Takaoka, 2002;Oh et al, 2007;Yan et al, 2010;Hu et al, 2013;Han et al, 2017;Hsieh et al, 2018). The characteristics and relationships of PCDD/Fs and chlorobenzenes as indicators have also been studied (Ballschmiter et al, 1988;Altwicker et al, 1992;Kato and Urano, 2001;Lavric et al, 2005;Yin et al, 2007;Gullett et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…PCDD/F contamination usually binds to organic and/or inorganic particles with a diameter of <10 µm. For lower diameter of organic/inorganic particles (<2.5 µm), the ratio of number of PCDD/F molecules bound to particles decreases by nearly 35 percent [24].…”
Section: Introductionmentioning
confidence: 99%